D’un lecteur à l’autre : emprunts et circulation de manuscrits à Rouen à la fin du Moyen Âge - Monique Peyrafort-Huin (Tabularia)
The sources for the circulation of books in Rouen during the fourteenth and fifteenth centuries are particularly rich, and for some of them are still waiting to be exploited, especially in terms of the transmission of texts.From a fragment of a “loan register” from Saint-Ouen (1372-1378) and the records of deliberations conserved for the chapter of Notre-Dame of Rouen (1367-1493), it is proposed here, for these two libraries, to analyse principally loans, but also other forms of book circulation (sales, exchanges…, excluding bequests and donations): what were the terms of manuscript loan? who benefited from the circulation of books? which texts circulated in Rouen at the end of the Middle Ages? One of the last points, which is only hardly evoked here, concerns the vocabulary used during the lending process.